Ecological turnover in neotropical freshwater and terrestrial communities during episodes of abrupt climate change. (May 2021) - Pérez, Liseth; Correa-Metrio, Alex; Cohuo, Sergio; González, Laura Macario; Echeverría-Galindo, Paula; Brenner, Mark; Curtis, Jason; Kutterolf, Steffen; Stockhecke, Mona; Schenk, Frederik; Bauersachs, Thorsten; Schwalb, Antje
ABSTRACT: The last 85, 000 years were characterized by high climate and environmental variability on the Yucatán Peninsula. Heinrich stadials are examples of abrupt climate transitions that involved shifts in regional temperatures and moisture availability. Thus, they serve as natural experiments to evaluate the contrasting responses of aquatic and terrestrial ecosystems. We used ostracodes and pollen preserved in a 75.9-m-long sediment core (PI-6, ~85 ka) recovered from Lake Petén Itzá, Guatemala, to assess the magnitude and velocity of community responses. Ostracodes are sensitive to changes in water temperature and conductivity. Vegetation responds to shifts in temperature and the ratio of evaporation to precipitation. Ostracodes display larger and more rapid community changes than does vegetation. Heinrich Stadial 5-1 (HS5-1) was cold and dry and is associated with lower ostracode and vegetation species richness and diversity. In contrast, the slightly warmer and dry conditions during HS6 and HS5a are reflected in higher ostracode species richness and diversity. Our paleoecological study revealed the greatest ecological turnover for ostracodes occurred from 62.5 to 51.0 ka; for pollen, it was at the Pleistocene/Holocene transition. Future studies should use various climate and environmental indicators from lake and marine sediment records to further explore late glacial paleoclimate causes and effects in the northern neotropics.